Strategi Sinergi dan Inovasi untuk Pariwisata Berkelanjutan di Desa Wisata Lewomada, Kecamatan Talibura, Kabupaten Sikka - Martina Rudolfa Da Mendez; Yuliana Onang; Kristina Sujila (Jurnal Nirta : Inovasi Multidisiplin, 2025)
Lewomada Tourism Village, Talibura District, Sikka Regency, has great potential to be developed as a sustainable tourism destination. However, challenges in the form of limited community skills, minimal innovation, and lack of synergy between stakeholders are the main obstacles. This program aims to overcome these challenges through synergy and innovation training based on digital marketing and development of tourism products based on local culture. The results show that synergy between stakeholders and mastery of digital marketing can increase community capacity and sustainable tourism promotion.